2017
DOI: 10.3390/genes8120355
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening of 43 Brazilian Families Diagnosed with Leber Congenital Amaurosis or Early-Onset Severe Retinal Dystrophy

Abstract: Leber congenital amaurosis (LCA) is a severe disease that leads to complete blindness in children, typically before the first year of life. Due to the clinical and genetic heterogeneity among LCA and other retinal diseases, providing patients with a molecular diagnosis is essential to assigning an accurate clinical diagnosis. Using our gene panel that targets 300 genes that are known to cause retinal disease, including 24 genes reported to cause LCA, we sequenced 43 unrelated probands with Brazilian ancestry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…those for which potentially pathogenic variant(s) were not detected using the TS approach) were analysed via additional mutation screening (as described in the Methods section). None of the patients in these families carried the c.2991 + 1655A > G intronic variant in CEP290 that is frequently identified in European, Australian, and Brazilian families with LCA 5 , 7 , 8 . Neither were any of the analysed patients shown to harbour rare variants in five recently discovered LCA-associated genes ( CCT2 , CLUAP1 , DTHD1 , GDF6 , and IFT140 ) 20 24 , nor in exon 15 of RPGR , which is an alternative exon called ORF15 that contains highly repetitive purine-rich sequences (Supp.…”
Section: Resultsmentioning
confidence: 94%
“…those for which potentially pathogenic variant(s) were not detected using the TS approach) were analysed via additional mutation screening (as described in the Methods section). None of the patients in these families carried the c.2991 + 1655A > G intronic variant in CEP290 that is frequently identified in European, Australian, and Brazilian families with LCA 5 , 7 , 8 . Neither were any of the analysed patients shown to harbour rare variants in five recently discovered LCA-associated genes ( CCT2 , CLUAP1 , DTHD1 , GDF6 , and IFT140 ) 20 24 , nor in exon 15 of RPGR , which is an alternative exon called ORF15 that contains highly repetitive purine-rich sequences (Supp.…”
Section: Resultsmentioning
confidence: 94%
“…The remaining nine manuscripts deal with genotype–phenotype correlations. They range from very large genotyping studies (e.g., the Target5000 study by Dockery et al [ 87 ]) to targeted genotyping studies in pericentral RP (Comander et al [ 88 ]) and early-onset RP and LCA families (Di Iorio et al [ 89 ] and Porto et al [ 90 ]). Brandl et al [ 91 ] studied two genes encoding homologous proteins (IMPG1 and IMPG2) that are mutated in vitelliform macular dystrophies.…”
mentioning
confidence: 99%
“…Two studies have already reported these variants, but they did not confirm or discuss the pathogenicity of c.247T>C (p.Phe83Leu) or c.560G>A (p.Gly187Glu) [22,46]; moreover, these two reported cases are Brazilian and are included in this study (family B and E probands). Based on current knowledge of these two RPE65 variants, no strong evidence has been identified, as there are no previously reported mutations which, regardless of nucleotide change, result in p.Phe83Leu or p.Gly187Glu, and no functional studies showing that these variants cause deleterious effects.…”
Section: Variant Analysismentioning
confidence: 87%
“…Both variants in this study have already been associated with rare recessive retinal dystrophies, each of which was identified in only one homozygous patient [22,46]. Therefore, the criterion regarding the identification of evaluated variants in trans with known pathogenic mutations was not met (ACMG/AMP pathogenic moderate level of evidence).…”
Section: Variant Analysismentioning
confidence: 95%
See 1 more Smart Citation